2022
DOI: 10.3390/machines10100914
|View full text |Cite
|
Sign up to set email alerts
|

Modeling, Identification, and Compensation Control of Friction for a Novel Dual-Drive Hydrostatic Lead Screw Micro-Feed System

Abstract: This paper investigates the transmission performance of a novel dual-drive hydrostatic lead screw micro-nano feed system (DDHLS) that can obtain extremely low speed. Firstly, the oil film liquid friction of hydrostatic transmission is modelled, and the calculation model of oil film dynamic friction is proposed based on the variable viscosity theory. Secondly, on this basis, combined with the LuGre friction model, a novel all-components refinement friction identification method (ACRFIM) for DDHLS was developed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…When subjected to complicated external dynamic loads, joint component substructures are prone to micro-vibration with multi-directional degrees of freedom (DOFs). The joints will be able to show off the crucial characteristic of flexible connections by storing and dissipating energy and demonstrating elasticity and damping [57][58][59]. Statistics indicated that joint factors like damping and stiffness account for 30% to 50% of stiffness and 90% of the CNCMT's dynamic performance damping.…”
Section: Major Identification Elementmentioning
confidence: 99%
“…When subjected to complicated external dynamic loads, joint component substructures are prone to micro-vibration with multi-directional degrees of freedom (DOFs). The joints will be able to show off the crucial characteristic of flexible connections by storing and dissipating energy and demonstrating elasticity and damping [57][58][59]. Statistics indicated that joint factors like damping and stiffness account for 30% to 50% of stiffness and 90% of the CNCMT's dynamic performance damping.…”
Section: Major Identification Elementmentioning
confidence: 99%
“…Because the proposed method could identify the structure of non-feed drive systems, the entire machine structure was divided into two parts, the casting and the feed drive system, as shown in Figure 2. The modeling method for the feed drive system is quite mature and has been proposed by many scholars [20][21][22][23]. In this study, the modeling was performed using four DOFs.…”
Section: Proposed Identification Of Dof and Joint Position Processmentioning
confidence: 99%
“…Lu Kaiyuan, Wu Weimin [1] proposed a novel electromagnetic lead screw for wave energy applications; KK Varanasi, SA Nayfeh [2] develop a model of lead-screw system dynamics; W Zhang, X Zhang, et al [3] studied the machine tool with both ends fixed ball screw; Fengqing Tian, Jianmin Zhu, et al [4] analyzed screw feed drive system; Shen Xin, Zheng Zhi et al [5] optimized the screw parameters; Wu Honghui, Liu Jianke et al [6] studied variable-lead rotor and established thermal process simulation model considering leakage; Cao Lin, Wu Jianjun et al [7] established a precise friction torque model based on double-nut 2-point contact ball screws; Blanchet TA. [8] modeled an elastic screw body; Li Y, Zhang L et al [9] simulated the forming process of lead screw high-speed cold roll-beating; Vahid-Araghi O, Golnaraghi F. [10] designed a sliding mode controller; Meruva K, Bi Z, Mueller D, et al [11] modeled and validated the wear and fatigue life of a lead screw actuator; Wu DS, Lai HY, et al [12] presented a systematic modelling procedure for producing high precision elliptic helicoid screw transmission systems; Ma S, Zhang T, Liu G, et al [13] developed an analytical model of the planetary roller screw mechanism; Lai HY, Chen CK, et al [14] presented a new circular helicoidal surface meshing model for producing high transmission performance lead screws; Liu Y, Feng X, et al [15] studied the transmission performance of micro-nano feed system of hydraulic screw; Jintanawan, T., et al [16,17] used MATLAB/Simulink to study the dynamic model of the lead screw; Hojjat, Y. and M.M. Agheli [18] studied the capabilities and limitations of roller-screw; Minh-Thuan, H., Y. Wu and T. Van-Quyet [19] proposed mathematical model that used for screw rotor honing with a variable lead.…”
Section: Introductionmentioning
confidence: 99%